Dynamic 3D Blood Pool SPECT Imaging Using a Full-Ring Multidetector CZT SPECT Scanner for Diagnosing Thoracic Aneurysm - Masahiro Koyama; Yohji Matsusaka; Masafumi Takahashi; Akira Seto; Ichiei Kuji (Clinical Nuclear Medicine, 2026)
An 85-year-old woman underwent chest computed tomography (CT) during follow-up for COVID-19 infection, which incidentally revealed a 31-mm mass below the tracheal bifurcation. Because contrast-enhanced CT was not recommended due to renal impairment, endoscopic ultrasonography was performed and demonstrated intralesional blood flow, suggesting a vascular lesion. Dynamic and static 99m Tc-human serum albumin-diethylenetriamine pentaacetic acid SPECT imaging using a full-ring multidetector CZT SPECT scanner was subsequently performed. Static images confirmed the vascular nature of the lesion, while dynamic 3D SPECT with 2-second serial acquisition and time-activity curve analysis demonstrated peak enhancement synchronized with the aorta, enabling definitive diagnosis of an aneurysm.